Pemaknaan Kriteria Kesahihahan Hadis Mu?ammad Nâ?ir Al-Dîn Al-Albânî dan Implementasinya dalam Penilaian Hadis - Farida, Umma (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2016)
This article aims to examine the theoretical framework of Mu?ammad Nâ?ir al-Dîn al-Albânî on ?adîth. It has been known that sometimes al-Albânî explicitly put some ?adîths into unsound classification, whereas some major ?adîth scholars put the ?adîth in valid and authentic condition. Through studying his book entitled Silsilat al-A?âdîth al-?a?î?ah and some other books, this articel finds that although in some cases his conclusion is quite different from other ?adîth scholars, he is still standing on the previous principles to determine the validity of ?adîth such like: chain continuity (itti?âl al-sanad), fair narrators (‘âdil) and having good intellectuality (?âbi?), safe from berration (shudhûdh) and trouble (‘illat), but at some points, he has made his own differentiation in defining those principals. Besides, al-Albânî has also given special attention to the validity of matn (the content of ?adîth), that the matn should not be contrary with the Qur’ân, sunnah ?a?î?ah (the valid tradition), logical reasoning, historical facts, sciences, and the practice of previous piety (salaf al-?âli?).